Air source heat pump/heat pipe domestic room heating system: Design and experimental research. (25th June 2021) - Xu, Shuxue; Chu, Zihao; Niu, Jianhui; Ma, Guoyuan
Highlights: A concept of new air source heat pump/heat pipe was proposed. The structure and design method of the new system were introduced. The heating COP of it can reach to 4.64. Abstract: This study presents a new equipment for domestic room heating, air source heat pump/heat pipe room heating system. Heat pipes used as heat radiators are connected in series and driven by condensers. The structure and design method of the new system were introduced in detail and an experimental new system was also developed. The design method was based upon the empirical formula of heat transfer and the thermal resistance of each part was comparatively analysed. The difference of saturation temperature of heat pipes and heat pump of the system were investigated experimentally in the actual test process of the prototype. The distribution characters of the heat pipe heat radiators surface temperature along the altitude direction were observed. The results demonstrated that the proposed system was capable for a long and stable operation under outdoor temperatures of −1.5 °C to 3.3 °C and indoor temperature of 20 ± 1 °C, also the heating coefficient of performance (COP) of the ASHPP system could reach 4.35–4.64.